Real-time Internet news browsing: Information vs. experience-related gratifications and behaviors - Zhang, Lingzi; Zhang, Weiyu (Computers in human behavior, 2013)
•Two categories of online news gratification, including information utility and usage experience, are identified.•Real-time news browsing behavior is quantified by coding screen videos.•News browsing behaviors are coded as platform selection, content exposure and presentation usage.•Linkage between different gratifications and different news browsing behaviors is established. This study utilized lab observations with 49 subjects to observe what users encounter and how users behave in real-time Internet news browsing. We analyzed users’ selection of news platform, exposure to different topics of news content, and usage of different presentation elements by coding the screen videos. In addition, survey data with the subjects allow us to explore the links between gratifications and Internet news browsing behaviors. Our analyses suggest that users exert their control through actively and selectively interacting with the news services at the platform, content and presentation level to fulfill their different gratifications. In specific, gratifications based on information utility and those based on usage experience show different relations with different kinds of news browsing behaviors. Both the theoretical and methodological contributions are discussed at the end of this paper.